Synthesis of Indolo-and Benzothieno[2,3-b]quinolines by a Cascade Cyclization of o-Alkynylisocyanobenzene Derivatives - Onnicha Khaikate (2020)
© 2019 American Chemical Society. A new synthetic approach for the synthesis of indolo[2,3-b]quinolines and benzothieno[2,3-b]quinolines has been developed by employing the freshly prepared o-alkynylisocyanobenzenes derived from o-alkynylformamide derivatives as substrates. The synthetic transformations involved chloride-ion-triggered 6-endo cyclization of o-alkynylisocyanobenzenes to generate 2-chloroquinolines in situ, which further cyclized intramolecularly with nitrogen or sulfur atom via a cascade process to provide the corresponding indolo[2,3-b]quinolines and benzothieno[2,3-b]quinolines, respectively, in moderate to excellent yields.